Ammunition supplies, new proposal of ammunition sufficiency - Zlatník, Daniel; Mares, Jaromir (Vojnotehnički glasnik / Military Technical Courier, 2020)
Introduction/purpose:The paper is one of the outcomes of the project in the area of ammunition supply and standard day of supply (SDOS) design for ACR needs. It discusses the current approach of determining the amount and composition of ammunition stocks. Possible solutions to increase efficiency are considered. The aim is to achieve greater objectivity of the planning process where operations management and crisis management are included. Methods: Basic scientific methods were usedtogether with specific methods such asthe target-oriented method (TOM) and the effort level method (LoE). Results: The result of the scientific research is to determine the effective ammunition stock of the battalion level in order to achieve higher objectivity of the planning process of conducting operations and coping with crisis situations. The authors deal with a description of the current system of ammunition supply creation in the Czech Armed Forces and NATO, strengths and weaknesses included. A new consolidated system is proposed to improve a stock pile planning process for effective provision and sustainment to achieve operational success and risk mitigation. Objectives from NATO and EU task forces and current operations have been taken into account. The research used the target-oriented method (TOM) and the effort level method (LoE). Conclusion: The result of the scientific research is to achieve higher objectivity of the planning process of conducting operations and coping with crisis situations.